Director Networks and Cost of Equity Capital: Based on “Busy Director Hypothesis” Analysis - Sai Qiu; Xin Sun (Discrete Dynamics in Nature and Society)
This paper uses the data of Shanghai and Shenzhen A-share-listed companies from 2008 to 2018 to construct the director networks as an indicator to explore the relationship between the company’s director networks and the cost of equity capital and the influence of nature of property rights and the ownership structure on the aforementioned relationship. The research results demonstrate that director networks cannot effectively reduce the cost of equity capital. This conclusion verifies the “busy director hypothesis.” With the increase in the director networks centrality, the increase in the cost of equity capital in non-state-owned listed companies is more significant compared with state-owned listed companies; equity concentration plays a significant negative regulatory role in the director networks centrality and affects the cost of equity capital. Compared with the networks centrality of independent director, the networks centrality of nonindependent director has a stronger negative effect on the cost of equity capital. This article broadens the perspective of corporate governance research and provides new ideas for listed companies to make financing decisions.